Amyloid oligomerization of the Parkinson's disease related protein α‐synuclein impacts on its curvature‐membrane sensitivity. Issue 4 (6th November 2018) - Gallea, José Ignacio; Ambroggio, Ernesto E.; Vilcaes, Aldo Alejandro; James, Nicholas G.; Jameson, David M.; Celej, María Soledad
Abstract: The amyloid aggregation of the presynaptic protein α‐synuclein (AS) is pathognomonic of Parkinson's disease and other neurodegenerative disorders. Physiologically, AS contributes to synaptic homeostasis by participating in vesicle maintenance, trafficking, and release. Its avidity for highly curved acidic membranes has been related to the distinct chemistry of the N‐terminal amphipathic helix adopted upon binding to appropriated lipid interfaces. Pathologically, AS populate a myriad of toxic aggregates ranging from soluble oligomers to insoluble amyloid fibrils. Different gain‐of‐toxic function mechanisms are linked to prefibrillar oligomers which are considered as the most neurotoxic species. Here, we investigated if amyloid oligomerization could hamper AS function as a membrane curvature sensor. We used fluorescence correlation spectroscopy to quantitatively evaluate the interaction of oligomeric species, produced using a popular method based on lyophilization and rehydration, to lipid vesicles of different curvatures and compositions. We found that AS oligomerization has a profound impact on protein‐lipid interaction, altering binding affinity and/or curvature sensitivity depending on membrane composition. Our work provides novel insights into how the formation of prefibrillar intermediate species could contribute to neurodegeneration due to a loss‐of‐function mechanism. Open Practices: This article has received a badge for *Open Materials* because it provided all relevant information to reproduce the study in the manuscript. The complete Open Science Disclosure form for this article can be found at the end of the article. More information about the Open Practices badges can be found athttps://cos.io/our-services/open-science-badges/ . Abstract : Development of the nervous system is carried out by complex gene expression programs that are regulated at both transcriptional and translational level. Disruption of those programs by gene mutations, alcohol or Zika virus results in neurodevelopmental syndromes that present with microcephaly, autism, intellectual deficits and/or progressive neurodegeneration. In this review, we present recent literature that argues for a role of dysregulated ribosomal biogenesis in pathogenesis of various neurodevelopmental syndromes. We also discuss potential mechanisms through which such dysregulation may lead to cellular pathologies of the developing nervous system. Open Science: This manuscript was awarded with the Open Materials Badge. For more information see:https://cos.io/our-services/open-science-badges/